The Pfam protein families database in 2019. Issue Volume 47:Issue D1(2019) (24th October 2018) - El-Gebali, Sara; Mistry, Jaina; Bateman, Alex; Eddy, Sean R; Luciani, Aurélien; Potter, Simon C; Qureshi, Matloob; Richardson, Lorna J; Salazar, Gustavo A; Smart, Alfredo; Sonnhammer, Erik L L; Hirsh, Layla; et al.
Abstract: The last few years have witnessed significant changes in Pfam (https://pfam.xfam.org ). The number of families has grown substantially to a total of 17, 929 in release 32.0. New additions have been coupled with efforts to improve existing families, including refinement of domain boundaries, their classification into Pfam clans, as well as their functional annotation. We recently began to collaborate with the RepeatsDB resource to improve the definition of tandem repeat families within Pfam. We carried out a significant comparison to the structural classification database, namely the Evolutionary Classification of Protein Domains (ECOD) that led to the creation of 825 new families based on their set of uncharacterized families (EUFs). Furthermore, we also connected Pfam entries to the Sequence Ontology (SO) through mapping of the Pfam type definitions to SO terms. Since Pfam has many community contributors, we recently enabled the linking between authorship of all Pfam entries with the corresponding authors' ORCID identifiers. This effectively permits authors to claim credit for their Pfam curation and link them to their ORCID record.